Language choice and code-mixing in a longitudinal study of an Estonian-English bilingual child - Baird, Piret (Taikomoji kalbotyra, 2024)
The input that bilingual children receive influences their language proportions, language development, and code-mixing. Most studies on these topics have included early bilinguals whose input proportions undergo large changes in early childhood and whose parents use the one-parent-one-language family language policy. This paper examines the input-output proportions of an Estonian-English bilingual child over a period of 2.5 years (2;3-5;01) using recorded spontaneous speech from a situation where the input language proportions did not change and where the family language policy was different from the one-parent-one-language policy that is presented in most studies: the family rotated the language they all spoke by the day of the week. Additionally, the child’s code-mixing rate and her MLU scores are investigated to provide an overview of these factors in an unstudied input situation. Lastly, it is analyzed whether code-mixing by older siblings influences the code-mixing rate of the younger sibling. The results indicate that in the early phases of language development the child uses all the linguistic resources available to her, and as her language develops, she responds more in the language of the conversation and code-mixes less. However, there is also a period where the child unexpectedly almost stops speaking in Estonian regardless of the unchanged input. The data shows that code-mixed utterances are the longest, hence supporting previous research findings and indicating that code-mixing is a tool that helps the child communicate better. Code-mixing by siblings does not show any signs of affecting the younger sibling’s code-mixing rate, though a more thorough analysis is necessary. Hence, the results indicate the importance of input and shed light on input effects in bilingual language acquisition in an understudied input situation.